2018
DOI: 10.1002/adfm.201801819
|View full text |Cite
|
Sign up to set email alerts
|

Natural Wax for Transient Electronics

Abstract: Emerging classes of bioresorbable electronic materials serve as the basis for active biomedical implants that are capable of providing sensing, monitoring, stimulating, and other forms of function over an operating period matched to biological processes such as wound healing. These platforms are of interest because subsequent dissolution, enzymatic degradation, and/ or bioresorption can eliminate the need for surgical extraction. This report introduces natural wax materials as long-lived, hydrophobic encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(140 citation statements)
references
References 42 publications
1
139
0
Order By: Relevance
“…Beeswax (CB01) and Candelilla wax (CB10) are two natural materials reported recently for applications in bioresorbable electronics. [ 33 ] Beeswax contains hydrocarbons (14%), monoesters (35%), diesters (14%), triesters (3%), hydroxy monoesters (4%), hydroxy polyesters (8%), acid esters (1%), acid polyesters (2%), free fatty acids (12%), free fatty alcohols (1%), unidentified constituents (6%). [ 34 ] Candelilla wax includes hydrocarbons (about 50%, chains with 29–33 carbons), esters of higher molecular weight (20–29%), free acids (7–9%), and resins (12–14%, mainly triterpenoid esters).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beeswax (CB01) and Candelilla wax (CB10) are two natural materials reported recently for applications in bioresorbable electronics. [ 33 ] Beeswax contains hydrocarbons (14%), monoesters (35%), diesters (14%), triesters (3%), hydroxy monoesters (4%), hydroxy polyesters (8%), acid esters (1%), acid polyesters (2%), free fatty acids (12%), free fatty alcohols (1%), unidentified constituents (6%). [ 34 ] Candelilla wax includes hydrocarbons (about 50%, chains with 29–33 carbons), esters of higher molecular weight (20–29%), free acids (7–9%), and resins (12–14%, mainly triterpenoid esters).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis of ester and anhydride derivatives in these biocompatible and bioresorbable materials leads to dissolution on timescales of several months in vivo, as described in previous publications. [ 33,36 ] The swelling ratio of natural wax increases with the amount of these derivatives. The water uptake in Beeswax tends to be larger than that in Candelilla wax.…”
Section: Resultsmentioning
confidence: 99%
“…All the discussed metals were deposited via vacuum‐based technologies, such as, chemical vapor deposition and sputtering. However, a huge interest is nowadays directed toward the development of new and low‐cost methods to reliably fabricate bioresorbable metal films, such as laser printing and metal nanoparticle‐filled conductive inks …”
Section: Bioresorbable Materials and Dissolution Chemistrymentioning
confidence: 99%
“…Won et al reported on the use of natural waxes as materials for long‐time and hydrophobic encapsulation in bio/ecoresorbable electronics. Soy, myrtle, and candelilla waxes, derived from soybeans (via soybean oil), myrica cerifera (myrtle), and candelilla shrubs, respectively, were tested.…”
Section: Bioresorbable Materials and Dissolution Chemistrymentioning
confidence: 99%
“…While silk has gained extensive popularity as a device substrate material in various transient systems, it is noted that the swelling of silk represents a long‐standing issue that can result in unwanted delamination prior to achieving the desired performance . Though hydrophobic above the LCST, a similar issue occurs when dealing with MC substrates in warm water.…”
Section: Introductionmentioning
confidence: 99%